Performance Target Revisions in Incentive Contracts: Do Information and Trust Reduce Ratcheting and the Ratchet Effect? - Bol, Jasmijn C.; Lill, Jeremy B. (The Accounting Review, 2015)
ABSTRACT In this study, we examine a setting where principals use past performance to annually revise performance targets, but do not fully incorporate the past performance information in their target revisions. We argue that this situation is driven by some principals and agents having an implicit agreement where the principal “allows” the agent to receive economic rents from positive performance-target deviations that are the result of superior effort or transitory gains by not revising targets upward, while the agent “accepts” target revisions by not restricting output when these revisions are the result of structural changes in the operation's true economic capacity. Although both the principal and the agent can benefit from an implicit agreement, we argue that for the implicit agreement to be maintainable, the principal either needs information on the cause of the performance-target deviation or there needs to be trust between the principal and the agent. Using archival data across multiple years and independent bank units, we find a pattern of ratchet attenuation and output restriction that is consistent with the existence of implicit agreements for those principal-agent dyads where information asymmetry is sufficiently reduced or mutual trust exists. Data Availability: Data used in this study cannot be made public due to a confidentiality agreement with the participating firm.